The Effect of Financial Literacy, Financial Technology and Income on Small and Medium Entreprise Financial Behaviour - Ulkhair, Nisa; Almunawar, Mohammad Nabil; Kumari, Shalu; Handayani, Desi; Siskawati, Eka (Economics, Business, Accounting & Society Review, 2023)
Effective organizational financial decision-making relates to management's financial literacy level. Small and Medium Entreprise (SME), which is generally a family company, has a relatively low level of financial literacy. Meanwhile, the development of financial technology makes it easier for SME to access financial services digitally. This study aims to determine the effect of financial literacy, financial technology and income on SME financial behaviour. This study used a quantitative approach. The data collection method is carried out through the distribution of questionnaires to respondents. The population in this study is SME located in the Payakumbuh City area, with 115 SME samples. Samples are obtained using probability sampling methods and simple random sampling techniques. The results of this study showed that financial literacy variables had a significant effect on financial behaviour, while financial technology and income variables had no influence on financial behaviour. The study also shows that financial literacy, financial technology and income together significantly influence financial behaviour.